Substations - Krieg, Terry; Finn, John.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This handbook offers the whole knowledge of high voltage substations from their design and construction to the maintenance and the ongoing management, the entire asset life-cycle. The content of the book covers a range of substation topologies: Air-Insulated, Gas-Insulated and Mixed Technology Switchgear Substations together with the essential secondary systems. Additionally specialized substations such as ultra high voltage (UHV), offshore substations for wind power plants and the use of gas insulated lines are included. The book includes topics, providing information for increased reliability and availability, asset management, environmental management aspects, and the adoption of appropriate technological advances in equipment and systems in substations. The book was written by more than 30 experts from around the world and assembled through the Cigré study committee on Substations. This guarantees that the book contains information that is based on the global exchange and dissemination of unbiased information for technical and non-technical audiences. Although there are other works containing references to Substations, this book is designed to provide a complete overview of the topic in one book, providing a valuable reference for anyone interested in the topic. .
Introduction -- Planning and Concept -- Air-Insulated Substations -- Gas-Insulated Substations -- Mixed Technology Switchgear Substations and Gas Insulated Lines -- UHV and Offshore Substations -- Secondary Installations -- Environmental Impact of and on Substations -- Substation Management Issues -- Future Trends.
Keywords: Electric power production; Transportation engineering; Traffic engineering; Electrical Power Engineering; Transportation Technology and Traffic Engineering; Mechanical Power Engineering